THE ANALYSIS OF TRANSLATION PROCEDURE OF ADVERBIAL PREPOSITION AND ITS TRANSLATION IN HARRY POTTER AND THE CURSED CHILD - Fitri Palupi Kusumawati; Lilis Setiawati (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
The aims of this research are to give some positive contribution to the future researcher especially who want to analyzed about translation procedure preposition and the research is expected to be a useful for the student especially those who want to analyze about translation procedure and preposition. This study uses qualitative data analysis. Qualitative research can be done through library and field research, this study applies library research. This method s applied by reading and studying some books concerning with the topic of the problem. The data of this study were analyzed by using two steps, first describing the translation procedure of adverbial preposition the researcher give the example of the translation procedure of adverbial preposition. The researcher write the translated version below the original one in form of sentences and put marks by underlying both the translated prepositions and the original ones. Second, finding out and analyzing the untranslated the translation procedure of adverbial preposition. The researcher found in the Harry Potter and The Cursed Child’s book that were a lot of translation procedure and the highest percentage found that word for word translation was the highest percentage with 39, 39% and literal translation was the lowest percentage with 21, 21%